2019
DOI: 10.1002/ps.5380
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of novel and traditional insecticides used for management of whiteflies on the parasitoid Encarsia formosa

Abstract: BACKGROUND Encarsia formosa Gahan is the most important parasitoid exploited for the control of whitefly pests of vegetable crops. However, the non‐target effects of recently developed insecticides for controlling whiteflies toward this biocontrol agent is little documented. Here we evaluated the susceptibility of E. formosa adults and juveniles to eight commonly used insecticides against whiteflies. RESULTS Residual toxicity tests on glass showed that E. formosa adults were susceptible (over 98% mortality aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 77 publications
2
19
0
1
Order By: Relevance
“…Therefore, our results suggested that flonicamid was the only insecticide of those tested that could reduce both the primary and secondary spread of TuYV. Flonicamid has been described as an insecticide that inhibits the feeding behavior of aphids within 0.5 h of treatment without noticeable poisoning symptoms, such as convulsion, and this antifeeding activity remains until the insect dies [64]. This fact is consistent with the long duration of nonprobing in flonicamid-treated plants (WDI: 21,299.8 ± 1582.7 s) compared with untreated plants (WDI: 5905.4 ± 977.8 s).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, our results suggested that flonicamid was the only insecticide of those tested that could reduce both the primary and secondary spread of TuYV. Flonicamid has been described as an insecticide that inhibits the feeding behavior of aphids within 0.5 h of treatment without noticeable poisoning symptoms, such as convulsion, and this antifeeding activity remains until the insect dies [64]. This fact is consistent with the long duration of nonprobing in flonicamid-treated plants (WDI: 21,299.8 ± 1582.7 s) compared with untreated plants (WDI: 5905.4 ± 977.8 s).…”
Section: Discussionsupporting
confidence: 54%
“…In IPM programs, chemical control should be selective towards the target pest species and ideally harmless towards nontarget beneficial organisms [61,62]. Several studies evaluated the toxicity of the insecticides used in the present work on nontarget organisms [63][64][65]. Some of these chemical compounds may have undesirable effects on specific biocontrol agents; therefore, their inclusion in sustainable IPM programs should be adopted with caution.…”
Section: Introductionmentioning
confidence: 99%
“…Insecticides have been widely used in tomato and other crops due to their effective pest control and rapid action against susceptible populations of B. tabaci 54 . However, environmentally safe approaches (e.g., combining natural enemies and selective products) should be prioritized to avoid a build‐up of insecticide resistance 11,55,56 . In our study, the B. tabaci population was able to increase when exposed to dry residues of BCO on tomato leaves.…”
Section: Discussionmentioning
confidence: 68%
“…Tecnología y Salud, 6(2) 2019, 149-157 Ciencia, Tecnología y Salud, 6(2), 2019, 98 tiametoxan, las cuales son empleadas en la producción de hortalizas de la región. Otras moléculas empleadas en la región que también han sido reportadas como dañinas para E. formosa son: abamectina, cyantraniliprole y sulfoxaflor (Wang et al, 2019). El empleo de estos podría estar afectando las poblaciones nativas de E. formosa reduciendo considerablemente sus poblaciones.…”
Section: Discussionunclassified